“Let them see your face, my child, and thus know the meaning of all things”: Unity, the Child, and the Natural World in Rabindranath Tagore’s The Crescent Moon - Alves, Alicia (SARE: Southeast Asian Review of English, 2018)
This essay explores how Bengali poet Rabindranath Tagore mediates his ideas about universalism and natural harmony through the figure of the unnamed child in his collection of poems, The Crescent Moon (1913). I argue that when the child crosses the borders of home/nature and earth/cosmos, he also extends these borders to reach out for unity with broader communities outside of his own. The child embodies this unity with others and openness to the world because his body is a part of nature and the cosmos. Thus, the child also blurs the boundary between body and nature and reflects a unity with the world as a whole. This relationship with the natural world is one that adults in The Crescent Moon do not possess to the same extent and is specific to the child. In this way, the child must lead the adults to see and to live this connection.